Bioprospecting for Brewers: Exploiting Natural Diversity for Naturally Diverse Beers - Cubillos-Riffo, F (John Wiley and Sons Ltd, 2019)
The burgeoning interest in archaic, traditional, and novel beer styles has coincided with a growing appreciation of the role of yeasts in determining beer character as well as a better understanding of the ecology and biogeography of yeasts. Multiple studies in recent years have highlighted the potential of wild Saccharomyces and non-Saccharomyces yeasts for production of beers with novel flavour profiles and other desirable properties. Yeasts isolated from spontaneously fermented beers as well as from other food systems (wine, bread, and kombucha) have shown promise for brewing application, and there is evidence that such cross-system transfers have occurred naturally in the past. We review here the available literature pertaining to the use of nonconventional yeasts in brewing, with a focus on the origins of these yeasts, including methods of isolation. Practical aspects of utilizing nondomesticated yeasts are discussed, and modern methods to facilitate discovery of yeasts with brewing potential are highlighted. © 2019 John Wiley & Sons, Ltd.